Anaesthesia practice in caesarean section deliveries in tertiary care institute of eastern Nepal - Anuja,; Poudel, Bandana; Acharya, Saru; Kafle, Gokul; Bhandari, Dinesh (Birat Journal of Health Sciences, 2024)
1a. Introduction: Caesarean section is the most frequently performed surgical procedure  in obstetrics. General anaesthesia and regional anaesthesia are the anaesthetic techniques of choice for caesarean delivery. There is a world-wide rise in caesarean section rate during the last three decades and has been a cause of alarm and needs an in-depth study.2a. Objectives: The objective of this study is to determine the pattern of anaesthesia practice in Caesarean Section delivery at a tertiary care centre of eastern Nepal.3a. Methodology: This cross-sectional study was conducted at a one of the tertiary care centre of eastern Nepal from 2078/04/11 to 2078/10/11. Patients who delivered by caesarean section were included in the study. Basic demographic data , clinical indications  and type of anaesthesia  administered were noted.4a. Results: Out of the total 1222 cases, 1180 (96.56%) were emergency caesarean and 42 (3.43%) were elective caesarean. On observing the indications, previous lower section caesarean section was found to be in most patients i.e. 300(24.54%), followed by fetal distress 204 (16.69%) and failed induction in 185 (15.13%). The spinal anaesthesia being the preferred choice, used in 1167 (95.49%) patients, followed by general anaesthesia in 53 (4.33%) patients and epidural anaesthesia 2 (0.16%) patients.5a. Conclusion: Spinal anaesthesia is the most frequently used form of anaesthesia for caesarean section. Majority of caesarean section are emergency.Keywords: Caesarean Section, Pregnancy, Spinal anaesthesia, Tertiary care centre